A daily positive work reflection intervention for psychological distress among Chinese nurses: a pilot randomized controlled trial - Zhang, Li; Xiao, Jian; Zhang, Anao; Zhang, Hui (Frontiers in Psychology, 2025)
BackgroundChinese nurses experience high level of psychological distress, which negatively impacts nurses' mental health. A daily positive work reflection intervention is a widely disseminated employee management program, designed to improve employee wellbeing. The program has shown promising results in management, but has rarely been tested in healthcare settings, such as among nurses.ObjectiveThe purpose of this study is to evaluate the efficacy of a daily positive work reflection intervention for psychological distress among Chinese nurses.MethodsThis study used a switching replication design and randomly allocated 205 nurses to two groups (i.e., the experimental group and the waitlist control group) with three waves of measurement at pre-treatment, immediate post-treatment (T2), and immediate post-treatment (for the control group after intervention switch, T3) for changes in psychological distress.ResultsIn addition to significant within group improvements over time for both groups, OLS linear regression with Full Information Likelihood Estimation revealed a statistically significant between group treatment effects across outcome domains, including psychological distress, b = 22.60, p < 0.001, g = 11.34, somatic symptoms, b = 6.79, p < 0.001, g = 6.56, depressive symptoms, b = 8.15, p < 0.001, g = 8.19, and anxiety symptoms, b = 7.69, p < 0.001, g = 8.23.ConclusionsResults suggest that a daily positive work reflection intervention is a feasible and promising intervention for decreasing Chinese nurses' psychological distress. The study used a convenience sample which led to a concern of external generalizability, and the study had limited evaluation of long-term change.